The Effect of Classic Music Therapy and the Qur'an Murottal on Patient Anxiety Levels Before Tooth Extraction - Citrayuli Nurkhasanah; Abdul Rochim; Dwi Kartika Apriyono (Jurnal Multidisiplin Madani, 2023)
Handling anxiety can be done pharmacologically or non-pharmacologically. Several non-pharmacological therapies that can be used to reduce anxiety levels include relaxation therapy, sound therapy, and aromatherapy. Some examples of sound therapy are classical music therapy and murottal Al-Qur'an. The Aim of this research is to determine the effect of classical music therapy and Al-Qur'an murottal therapy on the patient's anxiety level before tooth extraction by observing changes in blood pressure before and after listening to classical music and Al-Qur'an murottal. This type of research is quasi-experimental with a pretest-posttest design. The research sample consisted of 30 patients with indications for tooth extraction divided into 2 groups: the group that was given classical music therapy Sonata in D major for two pianos, and the group that was given murottal therapy Al-Qur'an Al-Insyirah Surah and its translation and then assessed blood pressure before and after giving classical music therapy and murottal Al-Qur'an therapy. The distribution of patient anxiety which is known through the MDAS-Modification questionnaire shows that anxiety is in the moderate category. The Paired T-test results on blood pressure values of each pre and post intervention treatment group showed a p-value for classical music systole was 0.132, classical music diastole was 0.148, Qur'an murottal systole was 0.000, and Al-Qur'an murottal diastolic was 0.000. The results of the Independent T-test on blood pressure values between the two pre and post-intervention treatment groups were p-value systole of classical music and murottal Al-Qur'an was 0.000, and diastolic classical music and murottal Al-Qur'an was 0.000. The conclusion is listening to classical music and murottal Al-Qur'an can reduce patients' anxiety before tooth extraction. Murottal Al-Qur'an reduces patient anxiety before tooth extraction better than classical music